A nonlinear analytical model for tensile failure prediction of pseudo-ductile composite laminates. (October 2022) - Xiang, Huabo; Zhang, Yinxiao; Chen, Yang; Pagani, Alfonso; Zhang, Chao
Abstract: In this study, the tensile nonlinear responses of composite laminates with ± θ n s and ± θ n / 0 s layups are investigated. An analytical model that integrates the progressive failure, shear nonlinearity, fiber rotation, and fragmentation is established to characterize the nonlinear tensile behavior. A nonlinear factor is used to describe the shear nonlinearity of the resin matrix, which is governed by shear stress, while progressive damage indexes are determined by normal stresses. The degree of fiber rotation and the fragmentation between layers are analytically formulated. Tensile results from experiments conducted in this study and from others in the literature are used to verify the model's prediction accuracy. The proposed model provides acceptably good predictions of nonlinear behavior for pseudo-ductile carbon fiber reinforced composite laminates. A sensitivity analysis shows that the dominant model parameter changes from axial modulus to shear modulus, and eventually to transverse modulus as the off-axial angle increases from 0° to 90°. Highlights: We propose a new analytical model for nonlinear tensile failure prediction of composites. The model synthetically integrates shear nonlinearity, fiber fragmentation and rotation, progressive failure. Nonlinear behaviors of pseudo-ductile laminates with various layups are precisely predicted. The model captures the transition of dominant parameters with ply angle.